Kinematics Simulation Analysis of Six-legged Upright Walking Robot based on Adams - Jiulei Zhang (Jixie chuandong)
The principle of a six-legged upright walking robot with dual-motor driven and crank connecting rod mechanism as driving system is analyzed. Firstly， by using the vector analytical method， the corresponding motion mathematical model of the walking leg mechanism is established and analyzed. Secondly， the motion trajectory modeling and simulation analysis of unilateral walking leg mechanism is carried out by using the virtual prototype analysis software Adams. Finally， a physical prototype is built to verify the feasibility and the correctness of the working principle， scheme design and virtual simulation results. The results show that， walking leg mechanism can meet to working requirements of six-legged walking mechanism， design scheme is feasible. The theoretical basis for the next dynamics analysis and optimization design is provided.